2012
DOI: 10.5603/fhc.2012.0062
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chronic alcohol intoxication and smoking on the activity of oral peroxidase

Abstract: Abstract:Peroxidase is the most important antioxidant enzyme in saliva. Through peroxidation of thiocyanate in the presence of H 2 O 2 , peroxidase catalyses the formation of bacteriocidic compounds such as hypothiocyanate. The purpose of this study was to evaluate the effect of chronic alcohol intoxication and smoking on the activity of oral peroxidase (OPO). A total of 37 volunteers participated in the study. This cohort consisted of 17 male alcohol-dependent smoking patients after chronic alcohol intoxicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…In alcohol abusers and smokers, there have been reported disturbed function of the salivary glands with concomitant decrease in the secretion of salivary proteins, impairment in the immune mechanisms such as phagocytosis, chemotaxis, increased production of peroxides, and impaired function and proliferation of B and T lymphocytes and production of immunoglobulins [3,8,15]. People who chew tobacco have decreased levels of lysozyme and lactoferrin and increased secretion of immunoglobulin A in their saliva [9,10], which indicates reduced innate and activated acquired immunity of the saliva. Persons addicted to alcohol have been reported to have lower output of lactoferrin (non-smokers) [10] and immunoglobulin A (smokers) [9], which, together with the reduced output of lysozyme in our study, indicated suppression of immunity mediators present in the saliva.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In alcohol abusers and smokers, there have been reported disturbed function of the salivary glands with concomitant decrease in the secretion of salivary proteins, impairment in the immune mechanisms such as phagocytosis, chemotaxis, increased production of peroxides, and impaired function and proliferation of B and T lymphocytes and production of immunoglobulins [3,8,15]. People who chew tobacco have decreased levels of lysozyme and lactoferrin and increased secretion of immunoglobulin A in their saliva [9,10], which indicates reduced innate and activated acquired immunity of the saliva. Persons addicted to alcohol have been reported to have lower output of lactoferrin (non-smokers) [10] and immunoglobulin A (smokers) [9], which, together with the reduced output of lysozyme in our study, indicated suppression of immunity mediators present in the saliva.…”
Section: Resultsmentioning
confidence: 99%
“…People who chew tobacco have decreased levels of lysozyme and lactoferrin and increased secretion of immunoglobulin A in their saliva [9,10], which indicates reduced innate and activated acquired immunity of the saliva. Persons addicted to alcohol have been reported to have lower output of lactoferrin (non-smokers) [10] and immunoglobulin A (smokers) [9], which, together with the reduced output of lysozyme in our study, indicated suppression of immunity mediators present in the saliva. Generally, both alcohol abuse and cigarette smoking produce a synergistic increase in the concentration of acetaldehyde in the saliva [9].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The increased activity of lysosomal glycosidases in the saliva of alcoholics is attributable to ethanol itself as well as alcohol metabolites, and may occur via many mechanisms: increased lysosomal membrane permeability, delayed removal of the enzymes from saliva, impaired trafficking of lysosomal hydrolases to organelles, enhanced synthesis of enzyme by activated leucocytes or leakage from damaged cells (Waszkiewicz et al, 2013). Therefore, in alcoholics, lysosomal and cellular membranes of the oral cavity tissues (including oral mucosa and salivary glands) may be damaged, and proteases together with glycosidases (including alpha amylase) may be transferred to cytosol, extracellular matrix, and to saliva (Waszkiewicz et al, 2012). To the contrary, some authors have noted a reduction in the activity of salivary alpha-amylase in case of acute administration of alcohol (Enberg et al, 2001;Rohleder and Nater, 2009).…”
Section: Journal Of Biology and Life Sciencementioning
confidence: 99%